Answer: The following set of equations has been provided: I 3x+5y=12… (ii) 5x+3y=4… (ii) We will use the method of elimination to solve the pair of equations that we have been given.
Therefore, by multiplying the first equation by three, we get the result 9x+15y=36. (iii)
Also, by multiplying equation (ii) by 5, we get
25x+15y=20
… (iv)
On subtracting (iii) from (iv), we get
(25x+15y)−(9x+15y)=20−36
∴25x+15y−9x−15y=−16
∴16x=−16
∴x=−1
On substituting the value of x in equation (ii), we get
5(−1)+3y=4
∴−5+3y=4
∴3y=4+5
∴3y=9
∴y=3
Thus, we get x=−1
and y=3
, i.e. (x, y) =(−1,3)
, which is a unique solution